Konten di Media Sosial Sebagai Sarana Pelestarian Kebudayaan pada Swara Gembira - Theja, Calista Takako; Sari, Wulan Purnama (Koneksi, 2025)
Swara Gembira itself is a forum or means for cultural arts creators, especially the younger generation to recognize and learn about the national culture of Indonesia. Swara Gembira is present to provide and educate the national art of Indonesian culture so that it is not forgotten and can be developed and consumed by the people of Indonesia and also provide devotion to love for the homeland to continue to advance and maintain for the sake of Indonesian cultural arts. This research examines how Swara Gembira introduces the richness of culture in Indonesia on social media and fosters a sense of love and pride in Indonesian culture on Instagram. Mass communication theory becomes the basic foundation of this research to see how Swara Gembira introduces cultural wealth in Indonesia through social media. The methodology used is Qualitative with data collection techniques through interviews, literature studies and documentation collected by researchers. After conducting the research, the researcher drew the conclusion that the creation of social media as a means of cultural preservation goes along with the development of ongoing trends, Swara Gembira designed the creation of social media with creative and innovative cultural arts content in order to create interesting content. Swara Gembira sendiri merupakan wadah atau sarana bagi para pencipta seni budaya khususnya para generasi muda untuk mengenal dan belajar mengenai budaya nasional bangsa Indonesia. Swara Gembira hadir memberikan dan mengedukasi karya seni nasional budaya Indonesia agar tidak terlupakan dan dapat dikembang dan dikonsumsi oleh rakyat bangsa Indonesia serta turut memberikan bakti cinta kepada tanah air untuk terus maju dan memelihara demi seni budaya Indonesia. Dalam penelitian ini meneliti tentang bagaimana Swara Gembira memperkenalkan kekayaan budaya yang ada di Indonesia di media sosial serta menumbuhkan rasa cinta dan bangga terhadap kebudayaan Indonesia Instagram. Teori komunikasi massa menjadi landasan dasar pada penelitian ini guna melihat cara Swara Gembira memperkenalkan kekayaan budaya di Indonesia lewat media sosial. Metodologi yang digunakan adalah Kualitatif dengan teknik pengumpulan data melalui wawancara, studi kepustakaan dan dokumentasi yang dikumpulkan oleh peneliti. Setelah melakukan penelitian, peneliti menarik kesimpulan bahwa pembuatan media sosial sebagai sarana pelestarian kebudayaan berjalan mengikuti perkembangan trend yang sedang berlangsung, Swara Gembira merancang pembuatan media sosial dengan konten-konten seni budaya yang kreatif dan inovatif agar terciptanya konten-konten yang menarik.